2017
DOI: 10.1016/j.scienta.2017.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Response of okra ( Abelmoschus esculentus (L.) Moench) and soil properties to different mulch materials in different cropping seasons

Abstract: a b s t r a c tThe type of materials used as mulch and season of application may determine its impact on soil physical and chemical properties and crop yield. Hence, field experiments were carried out during 2015 (dry) and 2016 (wet) cropping seasons to determine the effect of various mulch materials on soil properties, leaf nutrient composition, yield and growth of okra (Abelmoschus esculentus (L.) Moench). The experiment consisted of four mulch materials (a) Pueraria phaseoloides, (b) Mucuna pruriens, (c) Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
(20 reference statements)
3
28
0
2
Order By: Relevance
“…There was higher moisture in the first few weeks (month of May) of incorporation of the manures in 2018 compared with 2017 which may have led to better and quicker decomposition of the organic materials in 2018. Soil biological activities which causes degradation of organic materials is severely limited during limited moisture, but with the onset of the rains (2018), there is a flush in microbial activity 20 .…”
Section: Discussionmentioning
confidence: 99%
“…There was higher moisture in the first few weeks (month of May) of incorporation of the manures in 2018 compared with 2017 which may have led to better and quicker decomposition of the organic materials in 2018. Soil biological activities which causes degradation of organic materials is severely limited during limited moisture, but with the onset of the rains (2018), there is a flush in microbial activity 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Pradeepkumar et al (2017) indicate that the effect of organic nutrition was significant only when the dose was considerably improved or supplemented with different sources of manure, whose long-term sustainability depends on the quantity and quality of the organic fertilizers applied, yield of crops, and quality and price of the product. Top-dressing fertilization in the dry season and with leguminous crops in the wet season maximized the yields of okra in a study conducted by Adekiya et al (2017).…”
Section: Bmentioning
confidence: 96%
“…Some researchers have confirmed that soil mulching can lead to an increase in the soil organic matter content [33], which improves soil physical quality (soil ρ b and µ) because mulching reduces soil compaction through a decrease in soil moisture evaporation [34][35][36] because the humus formation, as well as the resultant water holding capacity, is increased [25,35]. Wu et al [37] and Wang et al [38] stated that mulching applications are significantly influenced by an increase in the soil temperature through a thermal transfer between the ambient surroundings and the soil.…”
Section: Introductionmentioning
confidence: 99%